Properties of rhombohedral pyrolytic boron nitride - Dedkov V. S.; Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Lopatin V. V. Vladimir Vasilyevich; Sharupin B. N. (1996, 1996)
В фонде НТБ ТПУ отсутствует